Tingkat Kemampuan Melempar Bola Pada Permainan Bocce Anak Tuna Grahita Ringan Peserta Didik Putri (SDLB) Negeri Wiradesa Kabupaten Pekalongan - Kresnapati, Pandu; Fatkhu Royana, Ibnu; Aji Setyawan, Danang (Journal of Physical Activity and Sports (JPAS), 2024)
Special Education is intended for students who experience difficulties in the learning process due to physical, emotional, mental, intellectual, or social disorders, or have extraordinary intelligence and talent potential (National Education System Law of 2003). Children with physical, cognitive, and behavioural disorders generally receive educational services at Special Schools (SLB), which are special schools for children with special needs. This study used a "One Group Pretest - Posttest" design with a sample size of 10 female students in elementary school. Before being given treatment, an initial measurement of gross motor skills was carried out on moderately mentally retarded students at SLB Negeri Wiradesa with light warm-ups. Furthermore, bocce games were given as a treatment to train gross motor skills. After that, re-measurements were carried out to see changes in gross motor skills, referred to as final tests. The results of the study showed that bocce games could improve the gross motor skills of moderately mentally retarded students in Physical Education subjects at SLB Negeri Wiradesa, especially for female students.